Analysis of Added Value And Development Strategy of Cocoa Agro-Industry Based Farmer Groups at Mulyo Jati Farmer Group Mojokerto District - Safira, Ilmiana; Aji, Joni Murti Mulyo (JSEP (Journal of Social and Agricultural Economics), 2024)
This study aims to examine the cocoa supply chain, the added value of chocolate products, and the development strategies for the cocoa agroindustry at IPK Kelompok Tani Mulyo Jati in Mojokerto Regency to improve farmers' welfare. This research emphasizes the important role of farmer groups and agroindustries in enhancing the added value of cocoa products through effective strategies. The research method used is quantitative, with purposive sampling for respondent selection and data collection through interviews, observations, and documentation. Data analysis was performed using supply chain analysis, the Hayami method, and SWOT analysis. The results show that the supply chain includes product flow from farmers to consumers, financial flow from consumers to farmers, and two-way information flow related to cocoa bean care, price, quantity, quality, and the selling price of processed products. The added value of chocolate bars (10 grams) and cocoa powder (100 grams) is Rp 464,967/kg and Rp 82,667/kg, respectively. The recommended development strategy for the cocoa agroindustry is positioned in the white area of the competitive matrix, implementing the S-O strategy, which maximizes strengths and opportunities by maintaining product quality, increasing promotion, and expanding business and market reach.